The evolution of resistance and tolerance as cancer defences. Issue 3 (11th March 2020) - Thomas, Frédéric; Giraudeau, Mathieu; Gouzerh, Flora; Boutry, Justine; Renaud, François; Pujol, Pascal; Tasiemski, Aurélie; Bernex, Florence; Maraver, Antonio; Bousquet, Emilie; Dormont, Laurent; Osterkamp, Jens; et al.
Abstract: Although there is a plethora of cancer associated-factors that can ultimately culminate in death (cachexia, organ impairment, metastases, opportunistic infections, etc.), the focal element of every terminal malignancy is the failure of our natural defences to control unlimited cell proliferation. The reasons why our defences apparently lack efficiency is a complex question, potentially indicating that, under Darwinian terms, solutions other than preventing cancer progression are also important contributors. In analogy with host-parasite systems, we propose to call this latter option 'tolerance' to cancer. Here, we argue that the ubiquity of oncogenic processes among metazoans is at least partially attributable to both the limitations of resistance mechanisms and to the evolution of tolerance to cancer. Deciphering the ecological contexts of alternative responses to the cancer burden is not a semantic question, but rather a focal point in understanding the evolutionary ecology of host-tumour relationships, the evolution of our defences, as well as why and when certain cancers are likely to be detrimental for survival.